Effects of Irisin and Exercise on Metabolic Parameters and Reproductive Hormone Levels in High-Fat Diet-Induced Obese Female Mice. (February 2018) - Bastu, Ercan; Zeybek, Umit; Gurel Gurevin, Ebru; Yüksel Ozgor, Bahar; Celik, Faruk; Okumus, Nazli; Demiral, Irem; Dural, Ozlem; Celik, Cem; Bulut, Huri; Ilkay Armutak, Elif; Baysal, Bulent; et al.
It has been documented that exogenously administered irisin (10 10 fibronectin-type III domain-containing 5 [FNDC5]), which is a new polypeptide hormone, induces the browning of subcutaneous fat and thermogenesis. In this study, effects of physical activity and exogenous administration of irisin were investigated on parameters related with reproduction and metabolism in the high-fat diet-induced obesity model of the female C57BL/6J mice. Sixty mice were gathered at age approximately 5 to 6weeks and were divided into 3 groups. Control group remained sedentary. Irisin group remained also sedentary but intravenously received 10 10 FNDC5-expressing adenovirus after 20 weeks. Exercise group performed treadmill after 6 weeks. All mice were sacrificed 22 to 23 weeks after the start of the study. There was a significantly greater Δ weight in the controls compared with the irisin and exercise groups ( P < .05). Glucose and insulin levels were significantly higher in the controls ( P < .05). The serum irisin level was significantly higher in the exercise group ( P < .05). Serum luteinizing hormone levels were significantly increased in the irisin group ( P < .05). Serum anti-Müllerian hormone levels were significantly higher in irisin and exercise groups ( P < .05). There were significant negative correlations between serum irisin levels and Δ weight and homeostatic model assessment of insulin resistance ( r = −0.327, r = −0.297, respectively; P < .05 for both). The numbers of primordial follicles per ovary were similar ( P > .05), whereas primary and secondary follicles per ovary were higher in the irisin and exercise groups compared with controls ( P < .05). Pharmacologic introduction of irisin may improve metabolic factors such as insulin sensitivity and obesity by promoting weight loss and consequently improving the reproductive potential.